Characterization of the parasporal inclusion of Bacillus thuringiensis subsp. kyushuensis. - Held, G A (1990)
Electron microscopy of Bacillus thuringiensis subsp. kyushuensis revealed that the parasporal inclusions are composed of a homogeneous center surrounded by a thick, electron-dense coating. Antibodies directed against the 135- and 65-kilodalton B. thuringiensis subsp. israelensis peptides cross-reacted with the 70- and 26-kilodalton peptides, respectively, of B. thuringiensis subsp. kyushuensis.